The Avalonian and Nashoba terranes, eastern Massachusetts, U.S.A.: an overview - Hepburn, J.; Hill, Malcolm; Hon, Rudolph (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1987)
Three major fault-bounded terranes comprise the eastern margin of the Appalachian Orogen In the vicinity of Boston, Massachusetts. Each has a distinctive geological history. The easternmost, the Boston-Avalon Zone, contains features common to Avalonlan terranes in the northern Appalachians. These Include voluminous Late Proterozolc (650-600 Ha) calc-alkaline granitic to dioritic plutons and related volcanic rocks associated with the "main phase" of Avalonian thermal activity. These are covered by a thin veneer of Late Proterozolc to Early Paleozoic sedimentary rocks and fluviatile Carboniferous basin deposits. This terrene can be divided into three subzones on the basis of the igneous rocks present, metamorpbic grade, and style of deformation. The metamorphism generally is no higher than the green-schist facles in the Boston area, but reaches the amphibolite faciea to the south and west. The metamorphiem ia generally assigned an Alleghanlan age although there is evidence for Late Precamhrlan deformation and metamorphism. To the west, across the Bloody Bluff fault zone is the Hashoba Block, a terrane largely underlain by mafic volcanic rocks and volcanogenlc sedimentary rocks. During the Ordovlclan-Silurlan this terrane underwent upper amphibolite facles metamorphism and was intruded by calc-alkaline intermediate plutons and metalunlnous to peralumlnous granites. Best of the Nashoba Block, across the Clinton-Newbury fault zone, is the Merrimack Trough, underlain by a thick sequence of flysch and calcareous flysch. Crosscuttlng Ordovician plutons establish an upper age limit for these sedimentary rocks and the ages of deformation and netamorphism. Because of differing Late Proterozolc - Early Paleozoic histories. It Is unlikely that the Boston-Avalon Zone and Nashoba Block could have been juxtaposed prior to the Mid-Paleozoic. Whether the Nashoba Block and Merrimack Trough represent separate terranee, a composite terrane joined in the Late Precamhrlan or Early to Mid-Paleozoic, or faulted portions of a single terrane remains to he determined.